Do introductory criminology textbooks cite the most influential criminologists? Estimating the “match” between what journals report and what textbooks discuss - Wright, Richard A. (American journal of criminal justice, 1996)
Using recent citation analyses of criminology journals and textbooks to estimate the “match” between what journals report and what textbooks discuss. Twentythree criminology textbooks published from 1989 to 1993 were ranked by how prominently they cite the 25 most-cited scholars in recent leading criminology journals. I suggest some reasons why criminology textbook authors extensively cite and discuss some influential scholars but not others, and conclude by noting several limitations to using citation analysis to estimate the match between journals and textbooks.